Retrograde Endovascular Approach for Treating Unruptured Basilar Apex Aneurysms: Two Case Reports and Review of Literature - Rotta, Marcus Alexandre; Dias, Guilherme M.; Rezende, André Luiz; Pahl, Felix H.; Oliveira, Matheus Fernandes; Rotta, José Marcus (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Background Treatment of target lesions when parent vessels are injured or diseased may be quite difficult. Moret et al have proposed an endovascular technique based on retrograde transcirculation approach through communicating vessels.Methods We report on the first Brazilian experience with retrograde endovascular approach, to the best of our knowledge.Results The two cases illustrate difficult anterograde approach techniques to treat basilar apex aneurysms. In the first case, tortuosity and angulation of both vertebral arteries associated to stenosis did not allow an anterograde approach. In the second case, after a SAH of a basilar apex aneurysm treated more than a decade ago with bilateral vertebral artery trapping, the patient underwent a retrograde approach.Conclusion For this approach, follow-up data are still lacking and complications are usually more common than in anterograde approach. Nevertheless, in select cases, it may be applied by experienced hands with acceptable risks when no other treatment option (surgical or endovascular) is available.
Keywords: endovascular; aneurysm; treatment